Traditions on energy transition: theoretical revisions and paradoxes in the territories of the Argentine puna where lithium is mined - Hessling Herrera, Franco David (2025)
[Introduction]: Energy transition has been imposed as a theoretical problem in strict linkage with the effects of global warming and extreme weather events. [Objective]: The aim of this paper is to systematize the main theoretical contributions on energy transition in three traditions: techno-economicist, socio-technical and philosophical-political. [Methodology]: A qualitative epistemological approach is employed, configured in the focus of ethnographic articulation. From this framework, the results of fieldwork and analysis of localities, communities and legal frameworks in Argentine provinces where lithium is exploited are presented. Then, the results were intertwined with the matrix of theoretical traditions described, presenting the complexity of the territories. [Results]: It is found that each locality has different scenarios and models of governance, although many times there are transnational companies that operate in the same territory. [Conclusions]: The value of theoretical traditions is recovered as an instrument of analysis driven from the perspective of the Latin American Global South, useful to reflect on specific cases of any place.